Chronicity and Sex Affect Genetic Risk Prediction in Schizophrenia - Meier, Sandra M.; Kähler, Anna K.; Bergen, Sarah E.; Sullivan, Patrick F.; Hultman, Christina M.; Mattheisen, Manuel (Frontiers in Psychiatry, 2020)
Schizophrenia (SCZ) is a severe mental disorder with immense personal and societal costs; identifying individuals at risk is therefore of utmost importance. Genomic risk profile scores (GRPS) have been shown to significantly predict cases-control status. Making use of a large-population based sample from Sweden, we replicate a previous finding demonstrating that the GRPS is strongly correlated with admission frequency and chronicity of SCZ. Furthermore, we were able to show a substantial gap in prediction accuracy between males and females. In sum, our results indicate that prediction accuracy by GRPS depends on clinical and demographic characteristics.